Peningkatan Pemahaman Konsep Matematika Pada Materi Bangun Ruang Dengan Model Pembelajaran Mind Mapping(PTK pada Siswa Kelas VIII di SMP Negeri 7 Sukoharjo Tahun 2016/2017) - Kholidah, Fitri Arif, Dr. Sumardi, M.Si (2017)
The purpose of this research is to improve understanding geometry concepts by applying mind mapping. This research used a classroom action research method with 3 cycles. The subject of this research were the 8th grade students SMPN 7 Sukoharjo consist of 34 students which consist 18 male students and 16 female students. The sources of data were 8th grade students, the 8th grade teacher, and teaching and learning activities. The technique of collection data through observation, field notes, test, and documentation. Based on the research analysis it can be concluded that : 1) students can able to restate a concept before action 7 students (20.6%) and after action 21 students (61%); 2) students can provide an axample of a concept before action 10 students (29.5%) and after action 24 students (70%); and 3) students can applying the concept in solving problems before action 8 students (26.5%) and after action 31 students (91%). The conclusion of this research indicates that through mind mapping method can increase understanding geometry concepts in 8th grade students of SMPN 7 Sukoharjo academic year of 2016/2017.